Diseño de una estrategia de comunicación para la gestión del contenido : caso de estudio, aseguradora del Sur. - Andrade Vásquez, Andrea Nicole (2018)
This product focuses on "digital culture", a lifestyle marked by massive digital communication, and human interaction through social networks, in virtual environments. Digital culture redefines the role of people about media, making them "consumers" and "prosumers", it means that people choose the information to consume, and also produce messages. Based on this new dynamic and digital content management, an archetype of a digital bulletin was developed. The contribution of this product designed since user's experience, is creating an insurance culture based mainly on prevention of risks, and a clear knowledge about the insurance that assured people have, through language common. The benefits of this product are the conscious use of insurance and especially the generation of new habits that contribute to the prevention of accidents and this can be reflected in a harmonious and respectful society for life and environment. The process of research and product design had as main actors: insurance brokers, insured and Aseguradora del Sur, who supported the strategy of a communication for insurance and risk prevention through email and social networks, participating for the beginning of an Insurance culture from the digital communication. Digital Communication is a tool for education in any sector so it must be managed in a creative, but above all, ethical and responsible manner.